Effect of soy lecithin on total cholesterol content, fatty acid composition and carcass characteristics in the Longissimus dorsi of Hanwoo steers (Korean native cattle) - Li, Xiang Zi; Park, Byung Ki; Hong, Byuong Chon; Ahn, Jun Sang; Shin, Jong Suh (Animal science journal, 2017)
This study aims to investigate the effect of soy lecithin on the total cholesterol content, the fatty acid composition and carcass characteristics in the Longissimus dorsi in Hanwoo steers. Hanwoo steers (24 head) were fed two diets: Control (CON) (concentrate + alcohol‐fermented feed (AFF)) and soy lecithin treatment (CON + soy lecithin at 0.5% of the AFF). Soy lecithin treatment increased average daily gain, serum concentrations of triglyceride, total cholesterol and high‐density lipoprotein‐cholesterol in the blood. A lower cholesterol concentration was found in the Longissimus dorsi for the soy lecithin diet compared to the CON diet. With respect to the marbling score and quality grade of Longissimus dorsi, soy lecithin supplementation significantly increased the C20:5n3, C22:4 and polyunsaturated fatty acids contents compared to the CON diet. Soy lecithin supplementation would alter the total cholesterol content, polyunsaturated fatty acid profile and meat quality of Longissimus dorsi.